44. EVALUATION OF THE EFFECTIVENESS OF PROPHYLACTIC ANTIBIOTIC USE IN ELECTIVE CESAREAN SECTION AT QUANG THANH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of prophylactic antibiotics in cesarean section and compare the benefits of prophylactic antibiotics with those of long-term antibiotic therapy. Methods: A prospective study of 312 patients who underwent cesarean sections with prophylactic antibiotics at Quang Thanh General Hospital from April 1, 2024, to October 13, 2024.Results: The study recorded an average age of 29.03 years, with the age group of 18-35 years accounting for the highest proportion (85.9%); the most common cause of cesarean section was a previous scar (38.4%); the average surgery time was 42 minutes; the majority (92.3%) had a hospital stay of 5 days post-surgery; two cases of superficial infections with symptoms of swelling, redness, and minor discharge at the incision site were recorded, accounting for 0.64%. Conclusion: Prophylactic antibiotics offer many benefits, such as reducing the risk of wound infection, lowering treatment costs, shortening hospital stays, reducing waste disposal costs, and saving labor.
Keywords: Prophylactic antibiotics; cesarean section; Quang Thanh General Hospital